PENGARUH CORPORATE GOVERNANCE, KINERJA KEUANGAN DAN ISRA TERHADAP LUAS PENGUNGKAPAN SUSTAINABILITY REPORT - Susanti, Yenik (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
This research is meant to analyze the influence of corporate governance, financial performance which ismeasured by using ROA and Indonesia Sustainability Reporting Award (ISRA) to the Indonesia sustainabilitydisclosure area with size and leverage as the control variable. The corporate governance variables which areapplied in this research are the size of board of commissioners, the proportion of independent commissioners, thesize of auditing committee, managerial stock ownership and institutional stock ownership. The results of thisstudy show that the size of board commissioners has no significant influence to the sustainability reportdisclosure; the proportion of independent commissioners has no significant influence to the sustainability reportdisclosure; the size of auditing committee has no significant influence to the sustainability report disclosure;managerial ownership has significant influence to the sustainability report disclosure; institutional ownershiphas no significant influence to the sustainability report disclosure; financial performance has no significantinfluence to the sustainability report disclosure; ISRA has no significant influence to the sustainability reportdisclosure; these two control variables in this research which are size and leverage have significant influence tothe sustainability report disclosure.Keywords: Corporate Governance, Financial Performance, ISRA, Sustainability Report, Size, leverage.